The use and sustainable development of marine animal drugs by the Kinh people in Beibu Gulf - Luo, Binsheng; Nong, You; Zhang, Ting; Zhang, Shuai; Hu, Renchuan (Frontiers in Marine Science, 2023)
the Kinh people of China have a long history of using traditional marine animal drugs for their daily medicinal needs. With the advent of modern medicine, however, there is a risk of losing the valuable traditional knowledge of marine animal drugs. Thus, this study aimed to document the types of marine animal drugs and related traditional knowledge of the Kinh people and explore the sustainability of their access to marine animal drugs. Through field investigations in the "Three Islands of Kinh," we collected ethnozoological data on 61 marine animal drugs belonging to 52 families across six animal phyla. Chordata and Mollusca are the most represented phyla, while Arthropoda, Echinodermata, Sipuncula, and Cnidaria are less represented. According to the analysis, animal meat is the most frequent medicinal part; decoction or making medicinal soup is the primary processing method for marine animal drugs, while internal administration is the primary mode of use of them among the Kinh people. Our statistical analysis revealed that nourishing was the most common purpose for the recorded marine animal drugs in the study area. Our study highlights the importance of preserving the traditional knowledge of marine animal drugs among the Kinh people, particularly as they develop other industries that may threaten their fishery-related knowledge. Additionally, our findings can aid in the rational formulation and development of marine drug resources.